Prevalence of Streptococcus pneumoniae serotype 6C among invasive and carriage isolates in metropolitan Salvador, Brazil, from 1996 to 2007 - Campos, Leila Carvalho (2009)
Fundação Oswaldo Cruz. Centro de Pesquisas Gonçalo Moniz. Salvador, BA, Brasil.